Antioxidant Effects and Potential Molecular Mechanism of Action of Limonium aureum Extract Based on Systematic Network Pharmacology - Yang, Zhen; Mo, Yanan; Cheng, Feng; Zhang, Hongjuan; Shang, Ruofeng; Wang, Xuehong; Liang, Jianping; Liu, Yu; Hao, Baocheng (Frontiers in Veterinary Science, 2022)
Oxidative stress is the redox imbalance state of organisms, involves in a variety of biological processes of diseases. Limonium aureum (L.) Hill. is an excellent wild plant resource in northern China which has potential application value for treating oxidative stress. However, there are few studies focused on the antioxidant effect and related mechanism of L. aureum. Thus, the present study combining systematic network pharmacology and molecular biology aimed to investigate the antioxidant effects of L. aureum and explore its underlying anti-oxidation mechanisms. Firstly, the antioxidant activity of L. aureum extracts was confirmed by in vitro and intracellular antioxidant assays. Then, a total of 11 bioactive compounds, 102 predicted targets and 70 antioxidant-related targets were obtained from open source databases. For elucidating the molecular mechanisms of L. aureum, the PPI network and integrated visualization network based on bioinformatics assays were constructed to preliminarily understand the active compounds and related targets. The subsequent enrichment analysis results showed that L. aureum mainly affect the biological processes involving oxidation-reduction process, response to drug, et al., and the interference with these biological processes might be due to the simultaneous influence on multiple signaling pathways, including the HIF-1 and ERBB signaling pathways. Moreover, the mRNA levels of predicted hub genes were measured by qRT-PCR to verify the regulatory effect of L. aureum on them. Collectively, this finding lays a foundation for further elucidating the antioxidative damage mechanism of L. aureum, and promotes the development of therapeutic drugs for oxidative stress.